PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN BELANJA MODAL TERHADAP KEMANDIRIAN KEUANGAN DAERAH - EVE IDA MALAU; Eka Pratiwi Septania Parapat (Politeknik Bisnis Indonesia, 2020)
The objective of the research was to analized the influence original local revenue and capital expenditure partially on the independence of local finance in districts/towns of North Sumatera Province. The population was 33 districts/towns of North Sumatera Province years of 2010-2017 and population will be used as sample. The data were processed by using panel data regression statistic method. The result of the research that original local revenue had positive and significant influence on the independence of local finance. Meanwhile, capital expenditure had negative and significant influence on the independence of local finance. Keywords : Original Local Revenue, Capital Expenditure, Independence of Local Finance.